2008
DOI: 10.1007/s10552-008-9225-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of NQO1, ALDH2, and CYP2E1 genetic polymorphisms, smoking, and alcohol drinking on the risk of lung cancer in Koreans

Abstract: Our result suggests that the risk of lung cancer is affected by smoking, alcohol drinking, and the genetic polymorphism of NQO1. In particular, genetic polymorphisms for NQO1, CYP2E1, and ALDH2 synergistically with cumulative smoking amounts and alcohol drinking levels interact in the carcinogenesis of lung cancer in Koreans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 36 publications
1
27
1
Order By: Relevance
“…Similarly, the NQO1 rs1800566 CT and TT genotypes combined were significantly associated with an increased risk of lung cancer (OR=1.42; 95% CI=1.01-2.01). However, it is biologically plausible that the NQO1 polymorphisms affect lung cancer risk (20), as NQO1 has anti-carcinogenic activities, even though an association between NQO1 rs1800566 and lung cancer risk has not yet been confirmed. Notably, a recent meta-analysis study identified no significant association with lung cancer overall (35); however, stratified analysis by histology revealed that the TT and CT genotypes combined were marginally associated with an increased risk of SCC (OR for the TT and CT genotypes combined vs. the CC genotype=1.20; 95% CI=1.00-1.43; P=0.05).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the NQO1 rs1800566 CT and TT genotypes combined were significantly associated with an increased risk of lung cancer (OR=1.42; 95% CI=1.01-2.01). However, it is biologically plausible that the NQO1 polymorphisms affect lung cancer risk (20), as NQO1 has anti-carcinogenic activities, even though an association between NQO1 rs1800566 and lung cancer risk has not yet been confirmed. Notably, a recent meta-analysis study identified no significant association with lung cancer overall (35); however, stratified analysis by histology revealed that the TT and CT genotypes combined were marginally associated with an increased risk of SCC (OR for the TT and CT genotypes combined vs. the CC genotype=1.20; 95% CI=1.00-1.43; P=0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the metabolism of carcinogens, accumulating evidence suggests that NQO1 may lead to lung cancer development by inflammation (20). A previous study demonstrated that inflammatory cytokines, including IL1β and TNFα, suppress NQO1 activity (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, CYP2E1 c1/c1 genotype was associated with a significant increased risk for lung cancer in smokers with alcohol drinking (49). The induction of CYP2E1 is influenced by alcohol metabolism and this effect participates in the metabolic activation of various carcinogens such as N-nitrosodimethylamine (5,50).…”
Section: New Candidates Of Susceptible Genesmentioning
confidence: 99%
“…Polymorphisms of CYP2C9 can effect the risk of bleeding complications (19) and the response to the antihypertensive effects of losartan (20). Polymorphisms of CYP2E1, together with cumulative smoking and alcohol consumption, and polymorphisms of NQO1 and ALDH2 have been synergistically associated with lung cancer in Koreans (21). Polymorphisms of CYP7A1 have been associated with baseline low-density lipoprotein (LDL) and HDL cholesterol levels and risk of coronary artery disease (22).…”
Section: Introductionmentioning
confidence: 99%